View from the Stoop: Exploring the Impact of Place on Learning in Social Movements - Marilyn Mckenley Parrish (Adult Education Research Conference, 2007)
Studies from the field of geography offer insightful perspectives about the impact of place within social movements. Issues such as the complex construction of space, contested discourse, and boundary setting, particularly relating to gender, are affirmed within oral history interviews with women of the Catholic Worker Movement.